Comparative Analysis of DOL Starting Method with VFD on 630 kW/3 kV SWRO PUMP Induction Motor - Safrizal, Safrizal (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2024)
Operational starting current of an induction motor can reach 5-7 times the nominal current (FLA) in steady state conditions. This is due to the small impedance and high Locked Rotor Current (LRC). During starting, the terminal voltage experiences a voltage drop with a duration of 0.5 cycles to 1 minute, known as voltage dip or voltage sag. High current will generate heat that can damage the motor itself, cause voltage drop in an electrical power system, and if the voltage drop exceeds the allowed tolerance, it can disrupt other systems. To determine the starting current of a 630 kW/3 kV induction motor, a simulation can be performed using the ETAP Power Station software. From the simulation results, the starting motor SWRO Pump using the DOL method had a current surge of 440% (4.4 times) of the FLA (Full Load Ampere) 726 A, resulting in a voltage drop of 6%, while the VFD (Variable Frequency Drive) method had a current surge of 110% of the FLA (Full Load Ampere) 181.5 A with a voltage drop of 0.2%. Both methods experienced similar voltage drops within the acceptable limit (<20%), but had different current surges. The research concluded that VFD is safer because high starting current can cause interference with other equipment and affect the life of the motor's windings. The choice of starting method should be appropriate for the specific application.